DISSEMINATION OF INFORMATION WITH REGARD TO RURAL POPULATION ECONOMY THROUGH RURAL LIBRARY: A CASE STUDY OF CHIKKABALLAPUR DISRICT - Kumar N S, Ravi; K N, Prasad (International Journal of Research -GRANTHAALAYAH, 2019)
Information is raw material used to derive the facts and figures, which can be used by the layman of the nation. The information dissemination is required to build up strong nation and to develop strong economy through the agriculture. The rural public libraries play a pivotal role in nation building by providing information to the rural public and it intern helps in to build up strong economy of the country. The article deals the type of respondents, their educational background, the rural libraries selected for the study, their economic background, their dependence on news channels etc.